Clinical Applications of Antimicrobial Peptides (AMPs): Where do we Stand Now? - Divyashree, Mithoor; Mani, Madhu K.; Reddy, Dhanasekhar; Kumavath, Ranjith; Ghosh, Preetam; Azevedo, Vasco; Barh, Debmalya (Protein and Peptide Letters, 2020)
In this era of multi-drug resistance (MDR), antimicrobial peptides (AMPs) are one of the most promising classes of potential drug candidates to combat communicable as well as noncommunicable diseases such as cancers and diabetes. AMPs show a wide spectrum of biological activities which include antiviral, antifungal, anti-mitogenic, anticancer, and anti-inflammatory properties. Apart from these prospective therapeutic potentials, the AMPs can act as food preservatives and immune modulators. Therefore, AMPs have the potential to replace conventional drugs and may gain a significant global drug market share. Although several AMPs have shown therapeutic potential in vitro or in vivo, in most cases they have failed the clinical trial owing to various issues. In this review, we discuss in brief (i) molecular mechanisms of AMPs in various diseases, (ii) importance of AMPs in pharmaceutical industries, (iii) the challenges in using AMPs as therapeutics and how to overcome, (iv) available AMP therapeutics in market, and (v) AMPs under clinical trials. Here, we specifically focus on the therapeutic AMPs in the areas of dermatology, surgery, oncology and metabolic diseases.
Keywords: Antimicrobial peptides (AMPs)